MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS IX B MELALUI STRATEGI PEMBELAJARAN COOPERATIVE TIPE JIGSAW DI SMP NEGERI 4 TAMBANG - Erdawati Erdawati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
To improve students learning outcomes in English lessons at third grade level B on material report text throughcooperative learning strategy type jigsaw in SMP N 4 Tambang in 2016. The purpose of this study is to improvelearning English in the third grade level B on material report text through cooperative learning strategy typejigsaw in SMP N Tambang in 2016. The methode of this research is action research in 2 cycles. The subject ofthis research is students third grade of level B in SMPN 4 Tambang amount 25 students. This research usingtechnique test, questionare, and observation. The rank mark of this test is 1 – 100. Techique data analysis used isusing technique calculate the average value of students learning outcomes, percentage of student mastery score,and percentage of students’ completeness score. The results of this study indicate there is an increase learningoutcomes by applying cooperative learning strategies type jigsaw with the following results. There is an increasein student learning outcomes, which in the initial test average student learning outcomes is 44,40 in the firstcycle increased to 61,12 then in second cycle increase become 71,2., there are increase of mastery students.Where in the initial test the number of students who complete only 0 % increased 76 % in cycle I then increasedagain to 84 % in cycle II there is a decrease in the number of the students who are not complete, where in theinitial test the number of unfinished students reached 100 % in the first cycle to 24 % then in cycle II decreasedagain to 16 % with other only 4 students get the value of 50 and more 21 get the value of 60 and above 60.